IMPACT OF PARTY AUTONOMY AND FAIR HEARING ON ASSESSMENT OF EVIDENCE IN INTERNATIONAL ARBITRATION - McCarthy Mbadugha, Joseph N. (Teisė, 2016)
This article examines the impact of party autonomy and fair hearing on assessment of evidence in international arbitration and in consequence proffers some recommendations as a panacea for the negative impact of these concepts on assessing evidence and their consequences on award. The author is not aware of any previous studies in this area.It was found that evidence is assessed at the stage when parties and their legal representatives are not involved in the process and this has resulted, in some cases, in Arbitral Tribunals oversighting party autonomy and fair hearing. This has led to disruption of arbitration and several awards being set aside with consequent wastage of time and resources.The doctrinal research method was used. As a result this article examined the law in the area as it is and offered a critique in some instances and where appropriate provided an explanation of the law by placing it in a useful theoretical context. Primary sources (legislations, conventions and case–laws) as well as secondary literature in the area were studied in the theoretical and or conceptual dimensions of the articles